Relationship between cognitive impairment and hippocampal iron overload: A quantitative susceptibility mapping study of a rat model - Xi Deng; Meiru Bu; Jiali Liang; Yihao Sun; Liyan Li; Heishu Zheng; Zisan Zeng; Muliang Jiang; Bihong T. Chen (NeuroImage)
Background: The aim of this study was to establish an iron overload rat model to simulate the elevated iron levels in patients with thalassemia and to investigate the potential association between hippocampal iron deposition and cognition. Methods: Two groups of iron overloaded rats and one group of control rats were used for this study. The Morris water maze (MWM) was used to test spatial reference memory indicated by escape latency time and number of MWM platform crossings. The magnetic susceptibility value of the hippocampal tissue, a measure of iron deposition, was assessed by quantitative susceptibility mapping (QSM) and was correlated with spatial reference memory performance. The iron content in hippocampal tissue sections of the rats were assessed using diaminobenzidine (DAB)-enhanced Perl's Prussian blue (PPB) staining. Results: The rat groups with iron overload including the Group H and Group L had higher hippocampal magnetic susceptibility values than the control rat group, i.e., Group D. In addition, the iron overloaded groups had longer MWM escape latency than the control group, and reduced number of MWM platform crossings. There was a positive correlation between the mean escape latency and the mean hippocampal magnetic susceptibility value, a negative correlation between the number of platform crossings and the mean hippocampal magnetic susceptibility value, and a negative correlation between the number of platform crossings and the latent escape time in Group H and Group L. Conclusion: This rat model simulating iron overload in thalassemia showed hippocampal iron overload being associated with impairment of spatial reference memory. QSM could be used to quantify brain iron overload in vivo, highlighting its potential clinical application for assessing cognitive impairment in patients with thalassemia.